Tire Pressure Monitoring System Using Low-Frequency RFID Energy Harvesting - Sommart Lermthong; Surapan Airphaiboon; Sumek Wisavataksin (My University, 2023)
In this paper, we deploy the RFID technology for a tire pressure monitoring system (TPMS). RFID has the distinguishing feature for transmitting power wirelessly to a TPMS device. This enables the TPMS system to work battery-less and overcome the disadvantages associated with batteries. Our proposed system receives power from a low-frequency 134.2 kHz transmitter and stores it in a capacitor to enable the TPMS transponder. This power can successfully operate and transmit data from the sensor through the ultra-high-frequency 433 MHz to a reader installed inside the vehicle. The experimental results showed that it took only 34 seconds to charge the power when the reader distance was 6 cm, and the speed was 100 km/h.
Keywords: RFID technology advancements; Energy Harvesting in Wireless Networks; Internet of Things and Social Network Interactions